Integrated management of atrial fibrillation with digital health support: a pooled analysis of individual participant data from the mAFA-II and MIRACLE-AF trials - Gregory Y H Lip; Yang Chen; Mingfang Li; Yutao Guo; Minglong Chen (Cardiovascular Research, 2026)
Abstract Aims Adherence with a holistic or integrated care management of atrial fibrillation (AF) based on the AF better care (ABC) pathway has been associated with improved clinical outcomes. Two prospective randomized trials (mAFA and MIRACLE-AF) have evaluated this approach. The multicentre mAFA-II trial delivered the ABC pathway via mobile health using an mAFA App, while the MIRACLE-AF trial relied on village doctors supported by telehealth in rural communities. We conducted a pooled analysis of individual participant data to assess the overall efficacy of ABC pathway-based management in patients with AF. Methods and results We combined patient-level data from the mAFA-II and MIRACLE-AF trials. The primary endpoint was defined as a composite of all-cause mortality, ischaemic stroke, haemorrhagic stroke, heart failure (HF), acute coronary syndrome (ACS), and major bleeding events. The secondary endpoints included individual components and two grouped outcomes: all stroke and HF/ACS. A one-stage marginal Cox proportional hazards model stratified by trial and with robust standard errors clustered at the site level was used, with adjustment for CHA2DS2-VASc and other clinically relevant baseline variables. Cumulative event rates were estimated using Kaplan–Meier methods. Subgroup and sensitivity analyses were conducted to assess the robustness of the findings. Between-trial heterogeneity was further explored using a two-stage approach, incorporating trial-level effect estimates and inverse-variance weighting. We studied 4363 patients with AF [mean age 70.3 (SD 12.8) years; 60.5% male]. During 0.8 [SD 0.4] years of follow-up, the primary endpoint occurred in 329 (7.5%). Kaplan-Meier curves demonstrated lower cumulative incidence of events in the intervention group. On multivariable mixed-effects Cox models, the intervention group demonstrated a significantly lower risk of the primary endpoint compared to the control group (adjusted hazard ratio: 0.72; 95% confidence interval: 0.56–0.93). Subgroup analyses suggested potential effect modification, whereas sensitivity analyses consistently supported the primary findings. A two-stage analysis showed directionally consistent effects across trials for the primary endpoint. Conclusion In this pooled individual participant data from two prospective randomized trials, ABC pathway-based integrated care was associated with improved clinical outcomes in patients with AF vs. usual care, with the observed benefit primarily driven by reductions in HF/ACS-related events rather than classical AF-specific outcomes, supporting further implementation studies and context-specific adoption in clinical practice.